Formononetin, an active compound of Astragalus membranaceus (Fisch) Bunge, inhibits hypoxia-induced retinal neovascularization via the HIF-1α/VEGF signaling pathway - Wu J; Ke X; Ma N; Wang W; Fu W; Zhang H; Zhao M; Gao X; Hao X; Zhang Z (Dove Medical Press, 2016)
Jianming Wu,1–3,* Xiao Ke,2,* Na Ma,2 Wei Wang,2 Wei Fu,2 Hongcheng Zhang,2 Manxi Zhao,2 Xiaoping Gao,2 Xiaofeng Hao,2 Zhirong Zhang3 1Laboratory of Chinese Materia Medica, Department of Pharmacology, School of Pharmacy, Southwest Medical University, Luzhou, 2Post-Doctoral Research Station, Kanghong Pharmaceutical Group, 3Post-Doctoral Mobile Station, West China School of Pharmacy, Sichuan University, Chengdu, Sichuan, People’s Republic of China *These authors contributed equally to this work Background: It has been reported that formononetin (FMN), one of the main ingredients from famous traditional Chinese medicine “Huang-qi” (Astragalus membranaceus [Fisch] Bunge) for Qi-tonifying, exhibits the effects of immunomodulation and tumor growth inhibition via antiangiogenesis. Furthermore, A. membranaceus may alleviate the retinal neovascularization (NV) of diabetic retinopathy. However, the information of FMN on retinal NV is limited so far. In the present study, we investigated the effects of FMN on the hypoxia-induced retinal NV and the possible related mechanisms.Materials and methods: The VEGF secretion model of acute retinal pigment epithelial-19 (ARPE-19) cells under chemical hypoxia was established by the exposure of cells to 150 µM CoCl2 and then cells were treated with 3-(5'-hydroxymethyl-2'-furyl)-1-benzylindazole (YC-1, a potent HIF-1ɑ inhibitor, 1.0 µg/mL) or different concentrations of FMN (0.2 µg/mL, 1.0 µg/mL, and 5.0 µg/mL). The supernatants of cells were collected 48 hours later to measure the VEGF concentrations, following the manufacturer’s instruction. The mRNA expressions of VEGF, HIF-1ɑ, PHD-2, and β-actin were analyzed by quantitative reverse transcription polymerase chain reaction, and the protein expressions of HIF-1ɑ and PHD-2 were determined by Western blot analysis. Furthermore, the rats with retinopathy were treated by intraperitoneal administration of conbercept injection (1.0 mg/kg) or FMN (5.0 mg/kg and 10.0 mg/kg) in an 80% oxygen atmosphere. The retinal avascular areas were assessed through visualization of the retinal vasculature by adenosine diphosphatase staining and hematoxylin and eosin staining.Results: FMN can indeed inhibit the VEGF secretion of ARPE-19 cells under hypoxia, downregulate the mRNA expression of VEGFA and PHD-2, and decrease the protein expression of VEGF, HIF-1ɑ, and PHD-2 in vitro. Furthermore, FMN can prevent hypoxia-induced retinal NV in vivo.Conclusion: FMN can ameliorate retinal NV via the HIF-1ɑ/VEGF signaling pathway, and it may become a potential drug for the prevention and treatment of diabetic retinopathy. Keywords: formononetin, angiogenesis, oxygen-induced retinopathy, vascular endothelial growth factor, hypoxia-inducible factor-1